Spirituality as a moral renewal of human behavior (Journal of Philosophy Culture and Political Science, 2018)
Spirituality as human quality characterizes meaning of individual’s behavior, mobilizes human comprehension values onobjective factors and existential needs. The main thing is that not only gaining knowledge and its diversity, but consciouslyunderstand the value of internal and external life of human, comprehension of high values as truth, goodness, beauty, freedom,morality. Forming own spirituality people realize them in their life.Key words: spirituality, moral essence of spirituality, values, spiritual and moral education.